2019
DOI: 10.1103/physrevb.100.104428
|View full text |Cite
|
Sign up to set email alerts
|

String and conventional order parameters in the solvable modulated quantum chain

Abstract: The phase diagram and the order parameters of the exactly solvable quantum 1D model are analysed. The model in its spin representation is the dimerized XY spin chain in the presence of uniform and staggered transverse fields. In the fermionic representation this model is the dimerized noninteracting Kitaev chain with a modulated chemical potential. The model has a rich phase diagram which contains phases with local and nonlocal (string) orders. We have calculated within the same systematic framework the local … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(49 citation statements)
references
References 75 publications
(108 reference statements)
6
43
0
Order By: Relevance
“…The effective Hamiltonian of the columnar ladder is mapped onto two equivalent dimerized XY chains in a staggered transverse field (45,46). Contrary to the previous case, the columnar ladder has identical spectra in the even and odd sectors, resulting in the two-fold degeneracy of the eigenvalues of the Hamiltonisan (40). As a consequence, the phase diagram of this case is simpler, since there are no regions in the parametric space where different orders in the even and odd sectors overlap, resulting in larger variety of phases in Fig.…”
Section: Columnar Laddermentioning
confidence: 99%
See 1 more Smart Citation
“…The effective Hamiltonian of the columnar ladder is mapped onto two equivalent dimerized XY chains in a staggered transverse field (45,46). Contrary to the previous case, the columnar ladder has identical spectra in the even and odd sectors, resulting in the two-fold degeneracy of the eigenvalues of the Hamiltonisan (40). As a consequence, the phase diagram of this case is simpler, since there are no regions in the parametric space where different orders in the even and odd sectors overlap, resulting in larger variety of phases in Fig.…”
Section: Columnar Laddermentioning
confidence: 99%
“…The line pursued in the present study is that the extended Landau theory which incorporates the notions of nonlocal (string) order [37] and spontaneous breaking of hidden symmetry [38], remains instrumental even for nonconventional orders [14,[39][40][41]. The local and nonlocal string order parameters in the extended formalism are related by duality, and probing a phase transition and related emerging order is a problem of appropriate choice of variables [14,[39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…A characteristic feature of topological insulator is the edge or surface states occurring in the topologically nontrivial phase characterized by the nontrivially topological index, and the existence of the topological phase transition is generally accompanied by the changes of the topological numbers [5][6][7][8] or a nonlocal string order parameter. [9][10][11][12][13][14][15][16] The edge or surface states are protected by the energy gap of the topological system, leading that the edge states are robust against the local disorder and perturbation. [1,2,[17][18][19] These novel properties enable the topological insulator to have various potential applications in topological quantum simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The simplest model for quasi-periodicity is the Harper model [56] with a cosine-like shaped potential, which has been considered in Kitaev chains [35,38,51,53]. It can also be demonstrated that this model is closely related to the anisotropic XY spin chain (AXYSC) through the Jordan-Wigner (J-W) transformation [57][58][59][60][61][62][63][64]. One is then interesting in more nontrivial case.…”
Section: Introductionmentioning
confidence: 99%